Risk of musculoskeletal disorders in upper limbs in dental students: Concordance of different methods for estimation of body angle - Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (2013)
Aims: The purpose of this paper was to evaluate the agreement among different methods used to estimate angular deviation of the body to determine the risk for development of upper limb musculoskeletal disorders in dentistry undergraduates. Materials and Methods: Students (n = 79) enrolled in the final year undergraduate course of the Araraquara School of Dentistry-Sγo Paulo State University-UNESP were evaluated. Photographs were taken of students performing clinical procedures. The work postures adopted by each student were evaluated by means of rapid upper limb assessment (RULA). The basis used to obtain the individual's final risk score is the measurement of the angular deviations in the neutral positions of the regions evaluated. Two methods were used to estimate the angular deviation of the body: Visual exam and Image Tool software. A RULA final risk score was attributed to each procedure the student performed (n = 333). Study of the agreement between the methods about risk of musculoskeletal disorders was conducted by means of Kappa (κ) statistics. The level of significance adopted was 5%. Results: Fair agreement (κ = 0.32) between the evaluated methods was verified. Conclusion: The risk for development of upper limb musculoskeletal disorders by dentistry undergraduates evaluated by using RULA was not in agreement with the results obtained by use of visual exam and Image Tool.